Antibacterial efficacy of diode laser on Enterococcus faecalis in root canal: An in vitro study - CHE Shun, GUO Wei (Kouqiang yixue)
Objective To investigate the effects of diode laser on the bactericidal effect of Enterococcus faecalis in root canal, the external surface temperature of root canal outer wall and the morphology of dentin tubules under different irradiation modes, power, time and days, and to find the appropriate clinical operation parameters and techniques. Methods The single tube permanent tooth roots with completed root tip development were selected and divided into continuous mode group and chopped mode group according to the irradiation method. The two groups were irradiated for 10, 20 and 30 s with power of 1.5, 2.0 and 3.0 W respectively, and were continuously irradiated for 3 d. The temperature of the outer wall of the root canal was measured in each group during the first day of irradiation, and the colonies of Enterococcus faecalis were counted after daily irradiation. After 3 days of irradiation, the dentin tubule morphology of the inner wall of the root canal was observed under scanning electron microscopy, and the opening rate and opening diameter of the dentin tubule were calculated. Results ①With the increase of power and the extension of time, the bactericidal rate increased; the external surface temperature of root canal wall increased, and the dentin tubules gradually melted from opening; the opening diameter gradually shrank, and the opening rate gradually decreased, until they were completely fused and closed. In addition, the above trend was more obvious in the continuous mode group than in the chopped mode group under the same parameter. ②There was a preservation point of bactericidal rate, and there was no significant difference between 2.0 W-30 s, 3.0 W-20 s and 3.0 W-30 s under two modes on the second day of irradiation (P>0.05). ③The safe temperature limit of the outer surface of the root canal wall (10 ℃) was reached at 1.5 W-30 s, 2.0 W-20 s, 3.0 W-10 s under continuous mode and 2.0 W-30 s under chopped mode. Conclusion Diode laser continuous irradiation of root canal 1.5 W-30 s or chopped irradiation of 2.0 W-30 s for 2 consecutive days can achieve excellent bactericidal effect and no damage to the root and surrounding tissues, and can play a better role in dentin tubule closure.